2011
DOI: 10.1016/j.otsr.2011.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic osteochondral transplantations in the knee joint, midterm results of the SFA multicenter study

Abstract: Autologous osteochondral mosaicplasty seems to be a reliable technique in the short and intermediate term. It has the advantage of being less expensive than reconstructive techniques, is a one-step surgical procedure and results in immediate restoration of cartilage surface. Nevertheless, this is a difficult technique, which may result in complications and requires articular harvesting. This technique is limited by the size of the defect to be treated. The primary indication is deep, small defects on the media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 30 publications
1
46
0
8
Order By: Relevance
“…The results are good and comparable to those reported by the literature review carried out by the Société Franç aise d'Arthroscopie (SFA) [17] and more recent series [20,28,29]. Solheim et al [19,29] reported less satisfactory longterm results.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results are good and comparable to those reported by the literature review carried out by the Société Franç aise d'Arthroscopie (SFA) [17] and more recent series [20,28,29]. Solheim et al [19,29] reported less satisfactory longterm results.…”
Section: Discussionsupporting
confidence: 85%
“…Few studies have examined the long-term results of knee mosaicplasty [18][19][20]. The objective of this study was to assess the results at a mean of 9 years of follow-up in a continuous series of patients operated between 2001 and 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Chondrocyte damage is minimized with an increased number of impacts but with less force [49]. The grafts should not be left proud, as this can lead to increased contact pressures and potential graft demise [50].…”
Section: Osteochondral Autograft Transplantmentioning
confidence: 99%
“…Outcomes for OATS procedures in patients with OCD of the knee are better in patients with smaller lesions and patients with lesions in the medial femoral condyle [50]. One study of 142 OATS procedures, 61 for OCD lesions reported 72.5 % good or excellent results at 8-year follow-up [50].…”
Section: Osteochondral Autograft Transplantmentioning
confidence: 99%
“…It is for these reasons that larger lesions are preferentially treated with allograft. Smaller lesions and lesions of the medial femoral condyle treated with OATS have better clinical outcomes than those of the lateral condyle or patellofemoral compartment [76]. Achieving surface congruency is technically challenging, especially with the use of multiple grafts, and inevitably results in fibrocartilage fill in the interstices.…”
Section: Osteochondral Autograft Transplant (Oats)mentioning
confidence: 99%